Implementasi E-Assessment Go Formative dalam Pembelajaran Ekonomi - Humayra, Syahda; Friyatmi, Friyatmi (Jurnal Ecogen, 2025)
This research aims to examine the differences between the application of Go Formative e-assessment and conventional assessment on student learning outcomes. The study was conducted at SMA Negeri 1 Tanjung Mutiara with the research subjects being 11th-grade students. This is a quantitative study using a quasi-experimental design with a posttest-only control group design. The research sample was selected using purposive sampling. The research instrument was a learning outcome test using the Go Formative application. The research hypothesis was tested using a independent sample t-test. The results show the study indicate that there is a difference in student learning outcomes between the use of Go Formative e-assessment and conventional assessment.